Cognitive impairment therapy user interface with regression model / Nadia Syuhada Zainor Amri - Zainor Amri, Nadia Syuhada (2019)
Multisensory room (MSR) is one of the therapy for patients with cognitive impairment. Cognitive impairment patients have an issues of interacting with sensory inputs. Therapy sessions take a long period to see the effectiveness this therapy. Therefore, there is need to improve the connectivity and data cqllection that allow data analytic. This project presented an open source user interface with multisensory room, connectivity for data storage and data analytic. The main objective of this project to develop an open source user interface for connected multisensory room. Second objective to provide a data storage for the collection data of multisensory room in every session. Third is to provide a regression model for the data from multisensory room to help doctor's observation and decision for next treatment. For the user interface, it will receive sensorial games data from microcontroller by serial port for every therapy session. Next, therapist will assist the patients during the therapy and monitored the patiënt by sensorial checklist and behaviour checklist by using the user interface. Then, from the user interface, all the data will automatically save in the Microsoft Excel. Therefore, by using artificial data that have been discussed with medicine team, Microsoft Excel will give the regression model for each data. Hence, the regression model will help doctor to do the decision for next treatment.